PERKEMBANGAN PARADIGMA ADMINISTRASI PUBLIK (New Public Administration, New Public Management dan New Public Service) - Alamsyah, Anggriani (JPP (Jurnal Politik Profetik), 2016)
Within the domain of public administration, several paradigms have emerged and developed such as new public administration, new public management and new public service. The word ‘new’ is labeled to complement service standard of public administration which previously focused on efficient, economical and coordinated management, as well as social equity. New public administration emphasizes on the values of efficiency, productivity and business into public sectors to enhance the existing circumstances of public bureaucracy which tended to be huge and over in number, inefficient and lack in public service performance and less attentive to the development and enhancement of public service. New public service refreshes the role of the government, which in new public management perspective plays as facilitator, to be more on public services. Mechanism to achieve the intended objectives is to establish coalition and partnership among the government, private sectors and civil society, to suit the agreed necessities. The development of these paradigms indicates that this discipline intensively and extensively undergoes self-enrichment in its research materials.